Characteristics and survival of children with acute leukemia with Down syndrome or other birth defects in New York State. (December 2018) - Qiao, Baozhen; Austin, April A.; Schymura, Maria J.; Browne, Marilyn L.
Highlights: 1.6% of acute lymphocytic leukemia (ALL) and 11.0% of acute myeloid leukemia (AML) were represented by children with Down syndrome (DS). None of the children with DS was diagnosed with ALL within one year of age. Children with DS were more likely to be diagnosed with AML at a younger age. Ten-year survival was comparable among three birth defects groups for ALL children. Ten-year survival varied considerably by the birth defect status for AML children. Abstract: Background: Acute lymphocytic leukemia (ALL) and acute myeloid leukemia (AML) among DS children have been studied extensively using data from clinical trials or institutional reports. The purpose of this study was to link population-based cancer and birth defects data to evaluate characteristics and survival of children with acute leukemia according to the presence of DS or other birth defects. Methods: ALL and AML cases diagnosed between 1983 and 2012 among children aged 0-14 years were obtained from the New York State Cancer Registry. Birth defect status (DS, other birth defects, or no birth defects) was determined by linking with birth defects data. Associations between birth defect status and demographic characteristics were evaluated using contingency table analysis. Ten-year survival was calculated by birth defect status and other potential prognostic factors. Cox proportional hazards regression analysis was also performed. Results: Among 2941 ALL children, 1.6% had DS, 3.8% had other birth defects, and 94.5% had no birth defects. Birth defect status was significantly associated with age at ALL diagnosis. Survivals were similar among three groups. Among 563 AML children, 11.0% had DS, 6.0% had other birth defects, and 83.0% had no birth defects. Children with DS were more likely to be diagnosed with AML at a younger age and showed the best survival. Conclusion: Age at leukemia diagnosis was significantly associated with the birth defect status. Comparable survival was observed for ALL children. However, AML children with DS demonstrated superior survival compared to children with other birth defects or no birth defects.